ANALYSIS OF THE PROOF OF THE ELEMENTS OF THE CRIME OF AGGRAVATED THEFT COMMITTED CONTINUOUSLY (A STUDY OF DECISION NO. 942/PID.B/2025/PN LBP) - Ari Kuanda; Herlina Hanum Harahap (Jurnal Ilmu Hukum dan Keadilan, 2026)
Based on the results of the study, it shows that the legal provisions for proving the elements of the crime of theft under aggravating circumstances carried out continuously (Case Study of Decision Number 942/Pid.B/2025/PN Lbp) have been determined in Articles 363 and 64 of the Criminal Code, Articles 183 to 189 of the Criminal Procedure Code. Obstacles to proving the elements of the crime of theft under aggravating circumstances carried out continuously are the limited accurate and strong evidence, the difficulty of proving the continuing and aggravating elements, negligence and incompleteness of the chronology of events. Solutions to proving the elements of the crime of theft under aggravating circumstances carried out continuously (Case Study of Decision Number 942/Pid.B/2025/PN Lbp) include requesting expert testimony, encouraging the collection of additional evidence, analyzing evidence comprehensively, comparing witness and suspect statements, using other supporting evidence, and reconstructing the incident.